Prevalence of Spontaneous Bacterial Peritonitis in Patients with Liver Cirrhosis with Ascites: Prevalence of Spontaneous Bacterial Peritonitis in Liver Cirrhosis with Ascites - Adil Choudary, Muhammad; Saeed, Najam-us-sehar; Javed, Salman; Nabeel shafqat, Muhammad; Mumtaz, Sheroze; Farooq, Hafsa (Pakistan Journal of Health Sciences, 2022)
Bacterial infections are considered a significant challenge in patients with cirrhosis. They account for 25%–46% of hospitalizations in patients with cirrhosis due to significant decompensation processes and are associated with substantial morbidity and mortality. Objective: To determine the prevalence of SBP in patients with liver cirrhosis and ascites. Methods: According to the inclusion criteria, 199 patients with cirrhosis and ascites were included in the study, regardless of the cause of cirrhosis (alcohol, HCV, HBV, autoimmune, cryptogenic, etc.). SBP frequency in cirrhotic with ascites was documented using a proforma. All data was entered into a proforma template. All patients were treated with respect to evaluate the prevalence of SBP in cirrhosis with ascites patients. The study was conducted at the Department of Medicine at Gujranwala Medical College-District Headquarters Hospital in Gujranwala. Total duration of study was six months. Results: In terms of patient age distribution, 49 patients (24.6%) were between the ages of 30 and 45, 150 patients (75.4%) were between the ages of 46 and 60. The cohort’s patients had an average age of 51.21± 6.61. 42.7% of the population (n = 85) was female, while 57.3% (n = 114) was male. SBP frequency was 32.2% in cirrhosis with ascites individuals. Conclusions: We concluded that 32.2% of participants with cirrhosis with ascites also had SBP. The mortality rate in these patients will be decreased by early diagnosis and treatment. Any patient with cirrhosis and ascites should have SBP ruled out.